Evaluation of Hydraulic Conductivity and Diffusion Coefficient of Unsaturated Soils from Experimental SWRC - Galaviz-González , J. R.; Horta-Rangel, J. M.; Rojas-Gonzalez, E.; Pérez-Rea, M. L.; Lopez-Lara, T.; Hernandez-Zaragoza, J. B.; Cabello-Suárez, L. Y. (Current Overview on Science and Technology Research Vol. 10, 2022)
Fine unsaturated soils change their water content due to climatic conditions, pipe failure, and other factors. These changes produce drying-wetting cycles that generate shrinkage-swelling cycles due to variations in soil suction and water content. Several theoretical models are used to estimate the hydraulic behavior of soils (hydraulic conductivity and diffusion coefficient) by fitting the SWRC. The fitting model precision depends largely on the accuracy of the experimental points of the SWRC and the fitting model. Because of this, it is advisable to simply use the experimental data from the SWRC to obtain the hydraulic behavior. Therefore, an algorithm based on a data table, which uses an interpolation method with variable increments, is proposed. The procedure approximates the experimental SWRC using a polynomial equation generated for each branch (drying and wetting). This procedure simplifies the indirect method and avoids errors caused by the SWRC fitting process because it does not require fitting parameters. The results show that the hydraulic behavior of soils can be predicted more precisely with the proposed method than with the traditional methods.